Airways obstruction and pulmonary capillary blood volume in children with sickle cell disease. Issue 7 (8th July 2013) - Wedderburn, Catherine J; Rees, David; Height, Susan; Dick, Moira; Rafferty, Gerrard F; Lunt, Alan; Greenough, Anne
Summary Objectives and Working Hypothesis Airways obstruction occurs in young children with sickle cell disease (SCD). Our aim was to test the hypothesis that increased pulmonary capillary blood volume at least in part explained the increased airways obstruction as this would inform which therapy might be most appropriate to treat the airway obstruction. Study design Observational study. Patient‐subject selection Twenty‐five SCD children and 25 ethnic origin matched controls were recruited. Methodology Respiratory system resistance, using impulse oscillometry at 5 Hz (R5 %pred), pulmonary capillary blood volume (Vc), alveolar volume (VA), and spirometry were assessed before and after bronchodilator (ipratropium bromide). Lung volume measurements were also made. Results The SCD children compared to the controls had a higher R5 %pred before (median 133 (range 88–181)% vs. 102 (83–184)%, P = 0.0046) and after (105 (79–150)% vs. 91 (64–147)%, P = 0.0489) bronchodilator and their median Vc/VA (ml/L) was higher before (26 (18–38) vs. 18 (14–28) P < 0.0001) and after (26 (19–41) vs. 18 (13–27) P < 0.0001) bronchodilator. There were similar decreases in R5 %pred post‐bronchodilator in the two groups, but no significant changes in Vc/VA in either group. Vc/VA correlated significantly with R5 %pred in the SCD children only. Conclusions Increased pulmonary capillary blood volume contributes to the increased airways obstruction in children with SCD, hence, bronchodilators may be of limited benefit in reducing their airways obstruction. Pediatr Pulmonol. 2014; 49:716–722. © 2013 Wiley Periodicals, Inc.